The Language of Propaganda in President Bush Jr. Political Speech - Akmal, Saiful; Habiburrahim, Habiburrahim; Muluk, Safrul; Zulfikar, Teuku; Ravi, Muhammad (Jurnal Ilmiah Peuradeun, 2020)
The study of this article was set out to identify the use of the language of propaganda in Bush’s political speech. It was purposed to clarify the propaganda techniques applied by Bush in order to have one point of view among the audiences. The study focused on how the techniques of propaganda occurred within Bush Jr.’s speech in which he attempted to explain the different sides of who is combating terrorism and who is performing terror. The material of analysis was the speech delivered by Bush Jr. in front of the Military Officers Association of America Meeting in 2006. This article then found that the propagandist tries to control the relationship between information and audiences’ mind through the usage of language in their political speech. It was argued that propaganda can also effectively work toward almost all types of audiences, whereas the strategy of propaganda was mostly creating a fallacious reasoning connection concerning the topics being discussed.